Localized acute generalized exanthematous pustulosis with amoxicillin and clavulanic acid - Ozkaya-Parlakay, Ashinur; Azkur, Dilek; Kara, Ateş; Yildiz, Yilmaz; Orhan, Diclehan; Cengiz, A Bülent; Ersoy-Evans, Sibel (The Turkish Journal of Pediatrics, 2011)
Acute generalized exanthematous pustulosis (AGEP) is a rare skin disorder, characterized by acute development of numerous, pin-head sized, nonfollicular pustules on erythematous skin, with high fever and neutrophilia. The condition is frequently caused by hypersensitivity reaction to drugs or viral infections. Diagnosis is established according to clinical and histological criteria. Herein, we report a 17-year-old girl with localized AGEP related to the use of amoxicillin-clavulanate.